Fishing Anti-Inflammatories from Known Drugs: In Silico Repurposing, Design, Synthesis and Biological Evaluation of Bisacodyl Analogues - Sylla-Iyarreta Veitia, Maite; Siverio Mota, Dany; Lerari, Vanessa; Marin, Marta; M. Giner, Rosa; Vicet Muro, Liliana; Rivero Guerra, Yankier; Dumas, Francoise; Ferroud, Clotilde; A. M. de Witte, Peter; D. Crawford, Alexander; J. Aran, Vicente; et al. (Current Topics in Medicinal Chemistry, 2017)
Herein is described in silico repositioning, design, synthesis, biological evaluation and structure-activity relationship (SAR) of an original class of anti-inflammatory agents based on a polyaromatic pharmacophore structurally related to bisacodyl (BSL) drug used in therapeutic as laxative. We describe the potential of TOMOCOMD-CARDD methods to find out new anti-inflammatory drug-like agents from a diverse series of compounds using the total and local atom based bilinear indices as molecular descriptors. The models obtained were validated by biological studies, identifying BSL as the first anti-inflammatory lead-like using in silico repurposing from commercially available drugs. Several biological in vitro and in vivo assays were performed in order to understand its mechanism of action. A set of analogues of BSL was prepared using low-cost synthetic procedures and further biologically investigated in zebrafish models. Compound 5c and 7e exhibited the best antiinflammatory activities and represent new promising anti-inflammatory agents for further preclinical development.
Keywords: Atom-based bilinear indices